Student Activity in Project-Based Learning (PjBL) Science Learning to Improve Student Learning Outcomes of Ranto Panyang I State Elementary School - Saputra, Januar; Sari, Siti Mayang; Kasmini, Lili (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2025)
This study uses a descriptive quantitative method by revealing the usefulness of the independent curriculum teaching module which has great potential to create a more innovative, inclusive, and relevant learning environment for students. The activeness of students can develop into creative, critical individuals who are ready to face future challenges. The purpose of the study is to improve student learning outcomes through the implementation of teaching modules which are stages of learning activities provided by teachers. Based on student learning outcomes reviewed from the activities and roles of teachers, it is 95.83% with a very high category. The average results obtained based on observations on this learning aspect are 89.58% with a very high category. The average obtained from observations on student activities is 79.16% with a high category. Student activities in learning using science teaching modules based on Project Based Learning (PjBL) are carried out effectively in accordance with learning objectives.